Film coating potential of okra gum using paracetamol tablets as a model drug - Ogaji, Ikoni; Nnoli, Obiageli (Asian Journal of Pharmaceutics (AJP), 2014)
The purpose of this work was to study the film coating potential of okra gum extracted from pods of Abelmoschus esculentus plant using paracetamol as a model drug. Core tablets of paracetamol were obtained from a pharmacy shop in the locality and the physicochemical properties such as weight, hardness, friability, and disintegration time were evaluated. Aqueous coating suspensions of okra gum and hydroxypropylmethylcellulose (0.6%w/v) were prepared and used to coat the tablets in Hi-coater.The coated tablets were evaluated for weight uniformity, diameter, thickness, hardness, friability, disintegration time, and moisture uptake at controlled humidity. The coating remained intact, durable, and resistant to chipping when challenged to catastrophic fall or rubbed on a white paper. The coated tablets had lower friability, increased disintegration time (24 min) compared to the core (3 min) and improved hardness, but there was no difference in the dissolution profile of the samples from the batches containing okra and hydroxypropylmethylcellulose as film formers. Changes were observed in some of the physicochemical properties of the formulations containing okra gum as with the known film former and it was convenient to conclude that these changes were due to the effect of the mechanical properties of the film formers. It was our conclusion that okra gum is a promising natural, biodegradable, cheap and eco-friendly film former in aqueous tablet film coating operation, particularly when masking of taste or objectionable odor in a solid dosage formulation is desired.